HOLISTIC INTEGRATION IN FOREIGN LANGUAGE EDUCATION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the Integrated Course in Foreign Languages (ICFL) as a comprehensive approach that combines all aspects of language learning into a unified instructional system. The model integrates grammar, vocabulary, reading, writing, listening, speaking, intercultural competence, and digital literacy. Unlike traditional segmented teaching, ICFL emphasizes meaningful communication, cognitive engagement, and real-life application [1]. The study also reviews modern frameworks such as CLIL, multimodal teaching, mobile-assisted learning, and sociocultural mechanisms. The contributions of Uzbek researchers to integrated methodology are highlighted, demonstrating how national pedagogical practices enrich modern approaches. The article provides practical insights for educators, learners, and curriculum developers.